Comprehensive evaluation of the antigenic impact of intra-genotypic human papillomavirus variant diversity on recognition by neutralizing monoclonal antibodies raised against lineage a L1 virus like particles. Issue 7 (10th July 2020) - Godi, Anna; Boampong, Dulcibella; Elegunde, Busayo; Panwar, Kavita; Fleury, Maxime; Li, Shaowei; Zhao, Qinjian; Xia, Ningshao; Christensen, Neil; Beddows, Simon
Abstract : Introduction. Naturally-occurring variants of Human papillomavirus (HPV) genotypes have been defined as lineages and sub-lineages, but little is known about the impact of this diversity on protein function. We have previously demonstrated that variation within the major (L1) and minor (L2) capsid proteins impact the susceptibility of HPV to serum antibodies elicited by vaccination and natural infection. Higher resolution mapping of variant residues, however, requires the availability of appropriate tools, such as type-specific monoclonal antibodies (MAbs). These empirical data will improve our understanding of the consequences of natural variation on capsid antigenicity. Methods. We investigated the susceptibility of 37 representative pseudovirus variants of HPV16, HPV18, HPV31, HPV33, HPV45, HPV52 and HPV58 to neutralization by type-specific murine MAbs raised against the A lineage of their respective genotypes. Homology models derived from available HPV L1 crystal structures were generated to permit mapping of variant residues onto the surface-exposed L1 protein for relevant variants Results. Type-specific lineage A-specific MAbs demonstrated differential reactivity against some, but not all, variants within its respective genotype. Some of these differences were minor (<4 fold) while some variants displayed orders of magnitude reduced sensitivity. These differences in antigenicity were mapped to a limited number of variant residues on the capsid surface. Conclusions. These data contribute to our understanding of HPV L1 variant antigenicity and may have implications for seroprevalence or vaccine immunity studies based upon L1 antigens.